Evaluación de timol para el control microbiológico sobre películas de pintura - Bogdan, Sofia Tamara (2014)
The microbial colonization is an issue of increasing concern inside buildings not only because of causing aesthetic damages in coatings but also for developing diseases in persons with low-defence systems or respiratory problems. In this sense, cleaning is fundamental to maintain the hygienic conditions and somecommercial products that help to prevent and eliminate moulds in coatings have been developed.The aim of this research was to study the performance of thymol onto paint films as a potential compound to be used in fungicide liquids to control the incidenceand spread of moulds. Thymol (2-isopropyl-5-methylphenol) is a monoterpene found as the main compound in various essential oils, such as thyme and oregano. Numerous "in vitro" studies have shown the good performance of this compound as an antimicrobial and disinfectant. Painted panels were placed on moistenedfilter paper in Petri and, a spore solution of A. alternata, an environmental fungus was inoculated onto the paint. Finally, a set of panels was sprayed with asolution of thymol and another set with a commercial product. Sprayed panels with the thymol solvent (ethanol) and not sprayed panels were used as controls.Petri dishes were incubated at 28 °C for 2 months. It was observed that the thymol spray inhibited the fungus growth onto painted panels, while the commercialproduct and the controls did not show inhibition. Therefore, thymol is a natural alternative to formulate products that help to prevent the development of mouldson painted surfaces.